Perceived relationship, reward and brand post as antecedents of customer engagement in social networking sites / Noraniza Md Jani, Mohd Hafiz Zakaria and Ramlan Mustapha - Md Jani, Noraniza; Zakaria, Mohd Hafiz; Mustapha, Ramlan (Universiti Teknologi MARA, Perlis, 2020)
The presence and focus of brand users are difficult to predict in the social networking sites (SNS) medium. Marketers are still compiling the tactics of administering customers and prospects due to the ever-present new challenges. Research on customer engagement confirms the importance of antecedents in the SNS platform. However, various theoretical and practical support were extremely difficult to obtain. This study intends to fill this shortage through the well-known partial least square (PLS) technique. The questionnaire data were obtained from 389 respondents who actively interacted with brands at a minimum of 2 years in the SNS channel. The findings have verified the contribution of perceived relationship, reward, and brand post as antecedents to customer engagement. In closing points, this manuscript discusses the conclusion and implications to strengthen future literature and industry blueprints.